2014
DOI: 10.1021/ie4028582
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Management of a Water–Gas-Shift Membrane Reactor for High-Purity Hydrogen Production and Carbon Capture

Abstract: This paper focuses on the thermal management of a hydrogen-selective low temperature water-gas-shift (WGS) membrane reactor for simultaneous high-purity hydrogen production and carbon capture. A mathematical model of the reactor is developed consisting of a set of first-order hyperbolic PDEs. Open-loop simulations under a step change in the syngas inlet composition reveal the existence of large temperature gradients along the reactor. A control strategy is proposed whereby multiple distributed cooling zones ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 43 publications
0
23
0
1
Order By: Relevance
“…6 The performance of membranes for gas separation is typically evaluated by measuring the permeability of single species (P x and P y ) and calculating the ideal selectivity of one component of a gas pair relative to the other (α xy = P x /P y ). It was found that polymers suffer a trade-off relationship between these two values so that highly selective polymers have low permeability and vice versa.…”
mentioning
confidence: 99%
“…6 The performance of membranes for gas separation is typically evaluated by measuring the permeability of single species (P x and P y ) and calculating the ideal selectivity of one component of a gas pair relative to the other (α xy = P x /P y ). It was found that polymers suffer a trade-off relationship between these two values so that highly selective polymers have low permeability and vice versa.…”
mentioning
confidence: 99%
“…Precombustion CO 2 capture via membrane separation has also been studied using nonlinear MPC [237] and a combination of MPC and PI control [238]. Thermal management of membrane reactors for CO 2 capture using nonlinear control has been studied in [239].…”
Section: Co 2 Capture and Sequestrationmentioning
confidence: 99%
“…In Table 1, catalyst bed properties and reaction kinetic parameters are taken from the study of [5]. The operating conditions are based on the study of [3]. As shown in [20] which is the extended study from [5], the numerical model was verified with the experimental data in [20].…”
Section: Numerical Parameters and Model Verificationmentioning
confidence: 99%
“…In the first stage of the industrial-scale process units, a high temperature (HT-WGS) packed bed reactor is used to exploit fast kinetic rates. The outlet stream of the HT-WGS reactor is cooled and fed to low temperature (LT-WGS) packed bed reactor where the temperature is beneficial towards the equilibrium henceforth leading to a high CO conversion [3] (see figure 1). …”
Section: Introductionmentioning
confidence: 99%